Hubungan Nursing Students Engagement Dengan Academic Burnout Pada Mahasiswa Program Studi Keperawatan - Yeni Nur Cahyani; Nurul Hikmatul Qowi; Masunatul Ubudiyah (Jurnal Keperawatan Muhammadiyah, 2026)
Academic burnout is a major problem for students because they have to face variousstudy demands that make them easily feel tired. This feeling of tiredness can beovercome by increasing motivation and involvement in study activities. Thepurpose of this study was to analyze the relationship between student engagementand academic burnout in nursing study program. The design of this study usedanalytical correlation with a cross-sectional approach. The sample of this study was104 students, taken using stratified random sampling technique. The independentvariable in this study was nursing students engagement while the dependentvariable was academic burnout. Data collection used the SCEQ and SBIquestionnaires. Data analysis used the Spearman rho test with SPSS software. Theresults of this study showed that most of the nursing students engagement ofstudents were in the moderate category as many as 56 (53.8%) and most studentshad academic burnout in the moderate category, namely 65 (62.5%). Based on theresults of the data above, a significance value of p = 0.000 (p <0.05) was obtainedwith a value (r) = -0.349 which means that there is a negative relationship betweennursing students engagement and academic burnout in nursing study program at theUniversity of Muhammadiyah Lamongan. Based on this research, it is expected thatnursing students can minimize the occurrence of academic burnout by increasingmotivation and can also make lectures interesting by creating a discussion space todiscuss material that is not well understood with friends in organizations or smallgroups of close friends with the aim of increasing student engagement.